2023
DOI: 10.3389/fcimb.2023.1113992
|View full text |Cite
|
Sign up to set email alerts
|

Skin infectome of patients with a tick bite history

Abstract: IntroductionTicks are the most important obligate blood-feeding vectors of human pathogens. With the advance of high-throughput sequencing, more and more bacterial community and virome in tick has been reported, which seems to pose a great threat to people.MethodsA total of 14 skin specimens collected from tick-bite patients with mild to severe symptoms were analyzed through meta-transcriptomic sequencings.ResultsFour bacteria genera were both detected in the skins and ticks, including Pseudomonas, Acinetobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Corynebacterium is a Gram-positive bacterium that has been identified in the skin of tick-bite patients and associated ticks through transcriptome sequencing [ 25 ]. Similarly, Arthrobacter is another Gram-positive bacterium, has been identified in field-collected Haemaphysalis ticks in our previous study [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corynebacterium is a Gram-positive bacterium that has been identified in the skin of tick-bite patients and associated ticks through transcriptome sequencing [ 25 ]. Similarly, Arthrobacter is another Gram-positive bacterium, has been identified in field-collected Haemaphysalis ticks in our previous study [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the Acinetobacter genus, where our study showed a weak association between abundance values and changes in parasite load (Fig 5), it is essential to consider that certain members of this genus, such as Acinetobacter baumannii, are clinically significant pathogens due to their antibiotic resistance profile. Additionally, they have been identified as prevalent components of bacterial communities on the skin associated with arthropod bites [84][85][86]. Hence, upcoming studies should focus on isolating this genus from CL ulcers, examining its antimicrobial resistance profile, and thoroughly assessing its role in various aspects of the disease's pathogenesis.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…These include Jingmen tick virus (JMTV) ( Qin et al., 2014 ), Mogiana tick virus (MGTV) ( Pascoal et al., 2019 ), Alongshan virus (ALSV) ( Wang et al., 2019 ), Guaico Culex virus (GCXV) ( Ladner et al., 2016 ), Mole Culex virus (MoCV) ( Pauvolid-Correa et al., 2016 ), Wuhan flea virus (WHFV), Wuhan cricket virus (WHCV), Wuhan aphid virus 1 and 2 (WHAV1 and WHAV2), and Shuangao insect virus 7 (SAIV7) ( Shi et al., 2016 ). Importantly, tick-borne jingmenviruses, including JMTV and ALSV, have been detected in human samples obtained from individuals bitten by ticks in Kosovo and China, underscoring their significant importance in public health ( Emmerich et al., 2018 ; Jia et al., 2019 ; Wang et al., 2019 ; Zhang et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%